Numerical simulation of a direct internal reforming solid oxide fuel cell using computational fluid dynamics method - Li, Jun; Kang, Ying-wei; Cao, Guang-yi; Zhu, Xin-jian; Tu, Heng-yong; Li, Jian (Journal of Zhejiang University. A. Science, 2008)
A detailed mathematical model of a direct internal reforming solid oxide fuel cell （DIR-SOFC） incorporating with simulation of chemical and physical processes in the fuel cell is presented. The model is developed based on the reforming and electrochemical reaction mechanisms, mass and energy conservation, and heat transfer. A computational fluid dynamics （CFD） method is used for solving the complicated multiple partial differential equations （PDEs） to obtain the numerical approximations. The resulting distributions of chemical species concentrations, temperature and current density in a cross-flow DIR-SOFC are given and analyzed in detail. Further, the influence between distributions of chemical species concentrations, temperature and current density during the simulation is illustrated and discussed. The heat and mass transfer, and the kinetics of reforming and electrochemical reactions have significant effects on the parameter distributions within the cell. The results show the particular characteristics of the DIR-SOFC among fuel cells, and can aid in stack design and control.